Penerapan Cyber Notary Dalam Meningkatkan Keamanan Dan Kepercayaan Transaksi Elektronik - Gayatri, Damella Chandra (PT Matra Cendikia Abadi, 2024)
Implementation of cyber notary technology has become an increasingly relevant topic in the context of improving the security and trust of electronic transactions. This article discusses the concept of cyber notary, its benefits in improving the security and trust of electronic transactions, and the problems associated with its implementation. This study uses a literature review research method. Based on the literature review, it is concluded that the success of implementing cyber notary technology is highly dependent on the development of an adequate legal framework, resolving technical challenges, and increasing public awareness. Through proper implementation, cyber notary technology can provide additional protection for electronic transaction actors and strengthen trust in the electronic transaction ecosystem. The benefits of cyber notary in increasing the security and trust of electronic transactions are very significant. Through strong identity verification, maintained data integrity, and valid authentication evidence, cyber notary provides additional protection for transaction actors. The use of cyber notary technology has a positive impact on strengthening security and trust in the electronic transaction ecosystem, which is key to driving sustainable digital economic growth. Keywords : Cyber Notary; Electronic Transactin; Security